Motion and Time Study for A Lathe Machine Under Varying Light Intensities - Dr. Amit Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For creating a conducive working condition in an industrial production center, sufficient and well-balanced illumination levels are essentially required. A variety of visual tasks may be needed at various points involving different activities. One of the important factors for the higher productivity and comfort levels of the workers is the quality and intensity of the illumination provided at the workplace. Safety and morale of the workers are improved, especially near rotating machines. To create a safe environment and security at the industrial workplaces balanced brightness ratios, glare control or strobe effect should be considered. With the provision of sufficient lightning, an industrial unit can increase productivity by 10% to 50% and reduce errors by 30% to 60%. A motion and time study was conducted for a lathe machine, in a busy workshop engaged in producing a standard job on a mass scale. Several sets of observations were taken under varying illumination levels (natural and artificial lighting combined). It has been observed that a certain range of light intensity is required for optimum output if other conditions remain the same. There is a considerable reduction in productivity if the light intensity is less or more than this standard range. The reduction is higher at lower ranges than the reduction in higher ranges of illumination.